Plain English Movement And Penman’s Criticism To Strengthening The Movement - Syafrani, Andi (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2018)
Abstrak: The plain English movement has been commencing for many decades. Recently, the movement has penetrated beyond English-speaking countries. Plain English involves the use of straightforward and clear language. Additionally, it uses modern and standard English. Penman’s criticisms range from the trivial aspect to the deeply critical concerning the communication approach in legal language. She has written essays reviling plain English in some journals such as: ‘Plain English: wrong solution to an important problem’. Keywords: Plain English, Movement, Criticism. Abstrak: Gerakan Bahasa Inggris telah dimulai selama beberapa dekade. Baru-baru ini, gerakan ini telah memasuki beberapa negara pengguna bahasa Inggris. Bahasa Inggris melibatkan penggunaan bahasa yang lugas dan jelas. Selain itu, menggunakan bahasa Inggris modern dan standar. Kritik Penman dalam hal ini berkisar dari aspek sederhana hingga kritis mengenai pendekatan komunikasi dalam bahasa hukum. Dia telah menulis esai yang mengkritik penggunaan bahasa Inggris Hukum yang sederhana dalam beberapa jurnal seperti: 'Plain English: solusi salah untuk masalah penting'. Kata kunci: Bahasa Inggris Biasa, Gerakan, Kritik. DOI: 10.15408/sjsbs.v5i1.7907